IGBT Temperature Field Monitoring Based on Reduced-order Model - Ziyu Zhou; Yi Sui; Xu Zhang; Chengde Tong; Ping Zheng; Mingjun Zhu (CES Transactions on Electrical Machines and Systems, 2023)
With the rapid development of the world economy, IGBT has been widely used in motor drive and electric energy conversion. In order to timely detect the fatigue damage of IGBT, it is necessary to monitor the junction temperature of IGBT. In order to realize the fast calculation of IGBT junction temperature, a finite element method of IGBT temperature field reduction is proposed in this paper. Firstly, the finite element calculation process of IGBT temperature field is introduced and the linear equations of finite element calculation of temperature field are derived. Temperature field data of different working conditions are obtained by finite element simulation to form the sample space. Then the covariance matrix of the sample space is constructed, whose proper orthogonal decomposition and modal extraction are carried out. Reasonable basis vector space is selected to complete the low dimensional expression of temperature vector inside and outside the sample space. Finally, the reduced-order model of temperature field finite element is obtained and solved. The results of the reduced order model are compared with those of the finite element method, and the performance of the reduced-order model is evaluated from two aspects of accuracy and rapidity.